Does that sound right? The effects of regulatory fit and nonfit headline frames on motivated information processing. Issue 3 (3rd July 2019) - Lee, Yu-Hao; Getz, Bruce; Xiao, Min
ABSTRACT: Feeling right or wrong about a message frame can be used as a heuristic to infer one's motivational state and determine the depth of information processing. Two experiments examined how individuals' regulatory fit/nonfit response to news headlines interact with their motivation to influence information elaboration and information seeking. Under high motivations, regulatory fit confirmed their state and increased time spent on the news, elaboration, and information seeking. However, under low motivation, regulatory fit decreased elaboration and information seeking. Instead, under low motivational states, nonfit headlines increased elaboration and information seeking. The study fills a gap in the cognitive mechanisms of framing effect by demonstrating that there exists a fast and intuitive framing effect through affective responses such as regulatory fit-ness.